Comparison of trauma-focused cognitive-behavioral therapy and theory of mind on increasing social competence among abused children - Abdulzahra Naami; Yadollah Zargar; Iran Davoodi; Vahid Farnia; Safora Salemi; Faeze Tatari; Maryam Khanegi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: In recent decades, the use of psychological methods has been considered to improve the barriers and challenges of abuse adolescent females. This study focuses on comparing the efficacy of trauma-focused cognitive-behavioral therapy (TF-CBT) and theory of mind (ToM) on social competence among abused children. MATERIALS AND METHODS: A clinical trial was performed with 39 abused children as the subjects of the study. Participants are residents in Ahvaz (Iran) host-family centers and were randomly divided into two groups of experimental subjects and control subjects. The data collection method utilized the Social Competence Questionnaire. Descriptive statistics, covariance analysis, and Tukey's post hoc test were used for the data analysis. RESULTS: Comparison of the groups showed that the average behavioral and cognitive competence increased in both TF-CBT and ToM groups, but the average emotional, social competence is significantly higher in the ToM group. It is also found that the average social motivational competence is significantly higher in the TF-CBT group than in the ToM group. CONCLUSION: TF-CBT and ToM can be effectively used to improve the social competence of abused adolescent females.